Howard Watkins' Retirement from Fresno-Merced Counties Legal Services Dinner at Yen Ching Restaurant - Watkins, Howard::::::::: (1985)
?, Kurt Hoff, Carolyn Phillips, Michael Kanz, Joanne Cordova and Leroy Cordova Boxed gift for Howard Watkins on table